Combined Antibiotic and Photodynamic Therapies in Pseudomonas aeruginosa: From Synergy to Antagonism - Amanda C. Zangirolami; Koteswara Rao Yerra; Vladislav V. Yakovlev; Kate C. Blanco; Vanderlei S. Bagnato (Antibiotics)
Background: Antibiotics remain the most effective option for combating infections. However, the situation has shifted from ideal to concerning, as bacterial resistance to antibiotics is increasing in both prevalence and strength. Objectives: This study explores the synergistic/antagonistic potential of combining antibiotic and photodynamic therapy (PDT) against Pseudomonas aeruginosa. Methods: We conducted in vitro experiments to observe the effect of the sequential application of antibiotics and photodynamic therapy with a time interval between them. The antibiotics used were ciprofloxacin, ceftriaxone, and gentamicin, and Photodithazine was employed as the photosensitizer, with the PDT performed at different light doses of 660 nm radiation. Results: The combined effect was highly dependent on the antibiotic. While for gentamicin, the combination of antibiotic and PDT treatment was always synergistic, for ciprofloxacin, it could be severely antagonistic. Each antibiotic exhibited a distinctive pattern of interaction with PDT. Gentamicin resulted in the largest enhancement in bactericidal activity combined with PDT, requiring lower antibiotic concentrations to achieve significant bacterial reduction. Ceftriaxone’s bactericidal action was less influenced by PDT intensity, maintaining a stable efficacy regardless of different PDT dosages. Conversely, the outcome of ciprofloxacin was highly dependent on the antibiotic concentration changing from synergic to antagonistic action. Conclusions: The findings advocate for the development of treatment protocols that combine antibiotics and PDT and necessitate the establishment of the criterion for the dosage and periodicity of administration of such combination protocols. The demonstrated results open the doors wide to new applications and opportunities to combat infectious diseases through the combined use of photodynamic therapy and antibiotics.